Cash operating income and liquidity management for feeder cattle operations - Elliott, B.D.; Langemeier, Michael R.; Featherstone, Allen M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Net cash flow measures the amount of cash remaining after all cash expense obligations are satisfied. This cash is available for additional farm investment, off-farm investment, family living, and additional debt repayment. A 5-year, average, monthly, cash-flow statement was used to determine net cash flow for 18 feeder cattle farms .Results indicate that excess cash was used primarily to invest in equipment, vehicles, and nonfarm assets. Investments in buildings increased moderately over the study period, while investment in land was minimal.
Keywords: Beef; Cash flow; Liquidity; Investment; Feeder cattle